New shear strengthening configurations of near-surface-mounted CFRP laminates for RC beams - Barros, Joaquim A. O. (2016)
The effectiveness of the near surface mounted (NSM) technique with carbon fiber reinforced polymer (CFRP) laminates for the shear strengthening of reinforced concrete (RC) beams has been demonstrated during the last decade. Analytical and numerical research indicate that this technique can be more effective if the CFRP laminates are installed deeper into the slits. However, the depth of the slits is conditioned by the thickness of concrete cover. Furthermore, relatively deep slits can only be executed if the height of the beam’s cross section is relatively large for assuring an effective bond transfer length for the CFRP laminates. Therefore, an experimental program composed of a series of RC beams of relatively high T cross section web was carried out to assess the effect of installing CFRP laminates deeper into the slits on the shear strengthening effectiveness. The experimental program is described, and the main results are presented and discussed. An analytical model is proposed for determining the contribution of the NSM CFRP laminates on the shear strengthening of RC beams considering the effect of introducing laminates deeper into slits. Furthermore, a 3D multi-directional fixed smeared crack model, which incorporates a constitutive model for simulating the softening behavior of the opening and sliding concrete fracture components, is used to simulate the tested beams. By performing a parametric study with this model, the influence of the geometric and mechanical properties of FRP laminates on the shear strengthening effectiveness of RC beams is assessed.